Classification and data mining - Giusti, Antonio; Ritter, Gunter; Vichi, Maurizio (Berlin : Springer-Verlag, 2013)
"This volume contains both methodological papers showing new original methods, and papers on applications illustrating how new domain-specific knowledge can be made available from data by clever use of data analysis methods. The volume is subdivided in three parts: Classification and Data Analysis; Data Mining; and Applications. The selection of peer reviewed papers had been presented at a meeting of classification societies held in Florence, Italy, in the area of "Classification and Data Mining"."--Back cover.
Pt. I. Classification and data analysis. Robust random effects models: a diagnostic approach based on the forward search / Bruno Bertaccini, Roberta Varriale ; Joint correspondence analysis versus multiple correspondence analysis: a solution to an undetected problem / Sergio Camiz, Gastao Coelho Gomes ; Inference on the CUB model: an MCMC approach / Laura Deldossi, Roberta Paroli ; Robustness versus consistency in ill-posed classification and regression problems / Robert Hable, Andreas Christmann ; Issues on clustering and data gridding / Jukka Heikkonen ... [et al.] ; Dynamic data analysis of evolving association patterns / Alfonso Iodice D'Enza, Francesco Palumbo ; Classification of data chunks using proximal vector machines and singular value decomposition / Antonio Irpino, Mario Rosario Guarracino, Rosanna Verde ; Correspondence analysis in the case of outliers / Anna Langovaya, Sonja Kuhnt, Hamdi Chouikha ; Variable selection in cluster analysis: an approach based on a new index / Isabella Morlini, Sergio Zani ; A model for the clustering of variables taking into account external data / Karin Sahmer ; Calibration with spatial data constraints / Ivan Arcangelo Sciascia -- pt. II. Data mining. Clustering data streams by on-line proximity updating / Antonio Balzanella, Yves Lechevallier, Rosanna Verde ; Summarizing and detecting structural drifts from multiple data streams / Antonio Balzanella, Rosanna Verde ; A model-based approach for qualitative assessment in opinion mining / Maria Iannario, Domenico Piccolo ; An evaluation measure for learning from imbalanced data based on asymmetric beta distribution / Nguyen Thai-Nghe, Zeno Gantner, Lars Schmidt-Thieme ; Outlier detection for geostatistical functional data: an application to sensor data / Elvira Romano, Jorge Mateu ; Graphical models for eliciting structural information / Federico M. Stefanini ; Adaptive spectral clustering in molecular simulation / Marcus Weber -- pt. III. Applications. Spatial data mining for clustering: an application to the Florentine Metropolitan Area using RedCap / Federico Benassi, Chiara Bocci, Alessandra Petrucci ; Misspecification resistant model selection using information complexity with applications / Hamparsum Bozdogan ... [et al.] ; A clusterwise regression method for the prediction of the disposal income in municipalities / Paolo Chirico ; A continuous time mover-stayer model for labor market in a northern Italian area / Fabrizio Cipollini ... [et al.] ; Model-based clustering of multistate data with latent change: an application with DHS data / Jose G. Dias ; An approach to forecasting beanplot time series / Carlo Drago, Germana Scepi ; Shared components models in joint disease mapping: a comparison / Emanuela Dreassi ; Piano and guitar tone distinction based on extended feature analysis / Markus Eichhoff, Igor Vatolkin, Claus Weihs ; Auralization of auditory models / Klaus Friedrichs, Claus Weihs ; Visualisation and analysis of affiliation networks as tools to describe professional profiles / Cristiana Martini ; Graduation by adaptive discrete beta kernels / Angelo Mazza, Antonio Punzo ; Modelling spatial variations of fertility rate in Italy / Massimo Mucciardi, Pietro Bertuccelli ; Visualisation of cluster analysis results / Hans-Joachim Mucha, Hans-Georg Bartel, Carlos Morales-Merino ; The application of M-function analysis to the geographical distribution of earthquake sequence / Eugenia Nissi ... [et al.] ; Energy consumption: gross domestic product causal relationship in the Italian regions / Antonio Angelo Romano, Giuseppe Scandurra.
Includes bibliographical references.
Keywords: Data mining; Statistical decision